Lifestyle Risk Factors and Hypertension on Students: a Cross Sectional Study - Martiningsih, Martiningsih; Novieastari, Enie; Gayatri, Dewi; Nursasi, Astuti Yuni; Hadi, Ella Nurlaella (Jurnal Kesehatan Prima, 2024)
The incidence of hypertension is likely to occur at an increasingly younger age. The incidence is mainly due to risk factors for unhealthy behavior and lifestyle in adolescents. The purpose of this study was to analyze behavioral and lifestyle risk factors that affect the incidence of hypertension in adolescents. This research design is a descriptive-analytic with the cross-sectional study. The subjects in this study were 407 respondents from 10 junior and senior high schools in Bima City. Independent variables were gender, age, some behaviors like smoking, alcoholic, drug abuse, exercise, and healthy diet, abdominal circumference, and body mass index. Whereas, the dependent variable covers the incidence of hypertension. Results: In this study, behavioral risk factors in adolescents that correlate with hypertension are body mass index, age, and smoking behavior. The omnibus test results p value = 0.018 (